2008
DOI: 10.1080/15563650701647405
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity ofMicrurus altirostris(Uruguayan coral snake) venom and its neutralization by commercial coral snake antivenom and specific antiserum raised in rabbits

Abstract: In this work, we studied the neuromuscular blockade caused by Micrurus altirostris venom (0.1-10 microg/mL) in indirect stimulated chick biventer cervicis and mouse phrenic nerve-diaphragm preparations and the ability of commercial antivenom (Instituto Butantan) and antiserum raised in rabbits to neutralize neurotoxicity and lethality in chicks and mice (LD(50) 0.042 and 0.255 mg/kg), injected i.m. and i.p., respectively, with venom (5 LD(50)):antivenom or antiserum mixtures (n = 6) of 1:1-1:2.5-1:5-1:10-1:20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 17 publications
3
17
0
9
Order By: Relevance
“…However, possible species differences in the affinity of this toxin for its receptors cannot be ruled out. Mipartoxin-I inhibited contractures to exogenous ACh, indicating a predominantly post-synaptic action through the blockade of cholinergic nicotinic receptor, as also suggested for other studies using Micrurus venoms (Goularte et al, 1995;Serafim et al, 2002;Abreu et al, 2008;Camargo et al, 2011;Renjifo et al, 2012). The post-synaptic action of mipartoxin-I was also indicated by the absence of fade in the response to tetanic indirect stimulation at 70 Hz.…”
Section: Discussionsupporting
confidence: 79%
“…However, possible species differences in the affinity of this toxin for its receptors cannot be ruled out. Mipartoxin-I inhibited contractures to exogenous ACh, indicating a predominantly post-synaptic action through the blockade of cholinergic nicotinic receptor, as also suggested for other studies using Micrurus venoms (Goularte et al, 1995;Serafim et al, 2002;Abreu et al, 2008;Camargo et al, 2011;Renjifo et al, 2012). The post-synaptic action of mipartoxin-I was also indicated by the absence of fade in the response to tetanic indirect stimulation at 70 Hz.…”
Section: Discussionsupporting
confidence: 79%
“…Specific Micrurus antivenoms, produced in Brazil by the Butantan Institute (São Paulo) and the Ezequiel Dias Foundation (Minas Gerais), are produced in horses immunized with the venoms of M. corallinus and M. frontalis 29 . However, some studies suggest that the neutralizing capacity of antivenoms may be improved by including venom from other Micrurus species in the venom pool used in the immunization protocol 1,10,15,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that some Bothrops venoms and their major toxins are typically myotoxic in rodents; however, neurotoxic effects have been also revealed in mouse and chick. The neurotoxicity was observed by the blockade of neuromuscular transmission, either presynaptically, in a dose range similar to that of elapid venoms, or postsynaptically (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%